Diversity management současný trend řízení - Brodský Zdeněk; Teturová, Vendula (Univerzita Pardubice, 2008)
At the present time there is an increasing workforce diversity and it is expected that this trend is going to continue in the 21st century as well. That is why the top managers from different organisations are trying to find the various approaches how to manage the diversity of working environment in the best way. There is a necessity to put the accent on efficiency. However it is not easy to assess the impact of work team diversity on employees‘ performance or on the future organisation development. The subject of this chapter is to make readers acquainted with the topic Diversity management and its effective model. Then there is a mention of the new agenda of Diversity management which supports the cooperation among the scientists and the people with the practical work experience. This text describes at the same time the benefits and the barriers of Diversity management.
Keywords: diversity; diversity management; effective model of diversity management